A MICRO-VARIATION ANALYSIS OF THE VERBAL STRUCTURE OF LUNGU AND NAMWANGA LANGUAGES - Pethias Siame; Kennedy Njenje Kangwa; Djalilova Malika Shuxratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The paper presents a micro-variations analysis of tense in Lungu which is classified as M14 and Namwanga classified as M22. Lungu is spoken in the Northern Province of Zambia while Namwanga is spoken in Muchinga Province of Zambia. The paper aims to establish the micro-variations in the verbal structure of Lungu and Namwanga languages. The article adopted the qualitative descriptive design and used interviews, document analysis and comparative methods to collect and analyse data. Using micro-variations and comparative Bantu morphology (CBM) framing, the paper identifies and compares the various categories of micro-variations of tense in the Lungu and Namwanga languages. The article also evaluates the similarities and micro-variations in the two languages. The study shows that tense in Lungu and Namwanga languages is as has been attested by other Bantu languages. The study establishes that tense in the two languages is mutually intelligible. The analysis also reveals that Lungu and Namwanga languages are genetically related and share common structural components of tense. Therefore, there are more morphological similarities in the verbal structure than micro-variations in the two languages in terms of form.